SOCIAL INTERVENTION PROGRAMMES AND ECONOMIC EMPOWERMENT OF WOMEN IN GHANA: A RURAL DEVELOPMENT PERSPECTIVE - Boasu, B. Y.; Bamora, F. N.; Mbe, B. A. (UDS International Journal of Development, 2023)
In Ghana, efforts by successive governments to assure basic income for the poor and the vulnerable, especially women, have resulted in the promulgation of various social protection policies. Recent studies however, have identified a number of challenges bedevilling these social intervention programmes. This study examined how the Livelihood Empowerment Against Poverty (LEAP) cash transfer has actually empowered women economically, using Bawku as a case study. Purposive and quota sampling techniques were used in selecting a combined 112 respondents in a case study design. Primary data were gathered through interviews. The study revealed that; the LEAP cash transfer has enabled 41(45.1%) women beneficiary to upkeep their families solely whilst further 24 (26.4%) share the home responsibilities with their husbands. The study found that the LEAP programme has helped improve the trading activities of 45.6% women beneficiaries whilst further 32.2% beneficiaries have either engaged and or expanded their crop farming activities, with another 13.2% depending on the cash transfer as direct remittance to support their families. Notwithstanding these gains, the study revealed that, the meagre nature of the LEAP cash transfer makes it tough for beneficiaries to fully cover the reasons for which it was given them. The programme is also bedevilled with undue delay and irregular payment schedules which invariably distort the business and expenditure plan of the beneficiaries. The paper recommends that the LEAP programme should be backed by an Act to ensure regular payment schedule and realistic amount of payment to beneficiaries in case donor funding ceases. Keywords: Social Protection, Poverty, Empowerment, Cash Transfer, Social Intervention